2021
DOI: 10.33545/gynae.2021.v5.i4d.992
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and perinatal outcome in obstetrical emergencies at Lal Ded hospital, Srinagar

Abstract: Objectives: To identify obstetric cases as emergencies needing critical care. To assess the varying clinical presentations and contributing factors for cases arriving as obstetric emergencies. To identify the need for hospitalization and admission to intensive care unit. To understand the various interventions requiredcritical care management, and its impact on future outcome of such admissions and to analyze the maternal and perinatal outcome of such obstetric emergencies. Material and Methods: 200 cases of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Our results were in concordance with the results obtained by Teng S et al, who reported that 60 percent of the subjects were of multi-gravid status [11] . In another study conducted by Mustafa Adelaja L et al, mean age of the subjects with obstetrical emergencies was 30 years [12] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results were in concordance with the results obtained by Teng S et al, who reported that 60 percent of the subjects were of multi-gravid status [11] . In another study conducted by Mustafa Adelaja L et al, mean age of the subjects with obstetrical emergencies was 30 years [12] .…”
Section: Discussionsupporting
confidence: 94%
“…Sepsis leads to 9.5% of maternal death. Indirect cases where severe anemia in 3 cases, pulmonary edema in 5 cases, ARDS in 2 cases and ARF in 1 case [11] . In another study conducted by [13] .…”
Section: Discussionmentioning
confidence: 99%